A Multi-Attribute Examination of Consumer Conformity in Group-Level Ordering*. Issue 1 (February 2018) - Lee, Jacob C.; Kim, Jungkeun; Kwak, Kyuseop
Using real data acquired from transaction receipts at a cafe, the present research examined individuals' menu choices made in a group setting. Building on previous research, the present research proposed and examined what we call the group referencing effect, and found that individuals' menu choices were more likely to conform to the precedent menu choices made by the others in their group. A unique empirical contribution of the present research is that conformity was assessed and emerged at two levels: end-choice level (whether the choices are the same) and attribute-level (whether the attribute(s) of the choices are the same, independent of whether the end-choice is the same; i.e., similarity). Theoretical and practical implications are discussed.